A laboratory guide to the anatomy of the rabbit - Craigie, E. Horne (Edward Horne), 1894-1989 (University of Toronto Press, 1966)
The present work does not in any way aim to replace Bensley's Practical Anatomy of the Rabbit, which has long since proved its value beyond question. The attempt has been to meet a need for a shorter and less detailed laboratory guide adapted to courses for which Bensley's Anatomy has been found too extensive. Classes for which the present book is designed have assignments of time for this subject varying from about twenty-four hours to about sixty hours. Some of them have two-hour periods and some have three-hour periods. Some, moreover, have need for special emphasis on certain parts which are of less immediate interest to others. Of the twenty-eight illustrations, fifteen are new and the remainder have been borrowed from Bensley's Practical Anatomy. Four of the latter were the work of the late Dr. Bensley, the rest were prepared by the present author.